Fertilizer subsidy and agricultural productivity in Senegal - Seck, Abdoulaye (International Food Policy Research Institute, 2016)
In a consistent effort to raise productivity and unlock the economic and social potential of the agricultural sector, the Senegalese government has implemented heavy subsidy programs, some of which target the use of inputs. This paper assesses the potential impact of the fertilizer subsidy on farmers' productivity. We use data envelopment analysis to generate efficiency scores, which are then related to the subsidy program using an endogenous treatment-regression model that accounts for potential endogeneity and self-selectivity issues. The results indicate that the subsidy program appears to be associated with increased efficiency, hence providing empirical support to the political will to revamp the program. The results also suggest ways to improve the effectiveness of the subsidy program, as well as additional policy options to further unlock the agricultural potential.